Method for metalizing back electrode of TOPCon solar cell
Through the method of accurate laser radiation and low -penetrating sintering, it solves the problem of difficulty in sintering control during the metalization of the traditional TOPCON solar cell back. stability.
Patent Information
- Application Number
- CN202411919637.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the metallization process of the back electrode of the traditional TOPCon solar cell, the sintering process is difficult to accurately control, resulting in damage to the anti-reverse layer, high contact resistivity and large composite current, which seriously affects the battery performance.
Using precise laser irradiation combined with a specific proportion of metal slurry system and low-penetration sintering method, the laser energy acts on the pre-sintered metal slurry to promote Ag-Si interdiffusion and form high-density, small-size point contacts. , precisely control the burn-through depth to prevent large silver crystals from penetrating the anti-reflection layer.
A significant improvement of the photoelectric conversion efficiency of solar cells, reducing the contact resistance and composite current of the back electrode, and increasing the opening voltage and filling factor of the battery. Compared with the traditional method, it can bring 0.1-0.2%of the battery conversion efficiency improvement Essence
Smart Images

Figure CN119364924A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of TOPCon solar cells, and in particular to a back electrode metallization method for a TOPCon solar cell. Background Art
[0002] TOPCon solar cells are tunnel oxide passivation contact solar cells based on the principle of selective carriers, and are an upgraded version of PERC / PERT solar cells. TOPCon cells use N-type silicon substrates, and form a passivation contact structure by preparing an ultra-thin silicon oxide layer and a doped silicon thin layer, which effectively reduces surface recombination and metal contact recombination, thereby improving cell efficiency. In the production process of TOPCon solar cells, back electrode metallization is one of the key steps.
[0003] The back electrode of TOPCon cells usually uses silver paste fine grid. Since the passivation contact structure solves the problem of metal contact with the silicon substrate, the back side no longer requires laser grooving + aluminum paste, but directly uses silver paste fine grid to achieve better contact effect and lower contact resistance. The back fine grid slurry (silver paste, burn-through type) needs to burn through the SiNx layer during the sintering process and contact the poly silicon layer. Therefore, it is crucial to control the burn-through depth to avoid damaging the poly silicon layer or affecting the contact effect. By optimizing the back electrode metallization process, the open circuit voltage and fill factor of the TOPCon cell can be further improved, thereby improving the conversion efficiency of the cell.
[0004] During the metallization process of the back electrode of a traditional TOPCon solar cell, the metal slurry penetrates the anti-reflection layer, but the sintering process is difficult to accurately control, resulting in damage to the anti-reflection layer. Problems such as high contact resistivity and large recombination current are often encountered, which seriously affect the battery performance. Therefore, the present invention provides a TOPCon solar cell back electrode metallization method to reduce the recombination current, improve the contact quality, and reduce material consumption. Summary of the invention
[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a method for metallizing the back electrode of a TOPCon solar cell.
[0006] A method for metallizing the back electrode of a TOPCon solar cell comprises the following steps: (1) Preparation of tunnel oxide layer and doped polysilicon layer: First, a tunnel oxide layer with a thickness of 1-2 nm is formed on the back of the TOPCon solar cell; a doped polysilicon layer with a thickness of 50-100 nm is deposited on the tunnel oxide layer; and an anti-reflection layer with a thickness of 5-30 nm is deposited on the polysilicon layer; (2) Metal slurry layer coating and preliminary sintering: Use screen printing to coat the metal slurry on the anti-reflection layer on the back to form a metal slurry layer with a thickness of 15-25 μm, and perform preliminary sintering in a nitrogen atmosphere at a preliminary sintering temperature of 150-300 °C; (3) Laser precision irradiation treatment: Use laser equipment to precisely irradiate the pre-sintered metal slurry layer, with a duration of 200ms-3s, a laser power of 5-10W, and a forward bias voltage of 0.5-1.5V; (4) Low penetration sintering to complete electrode metallization: low penetration sintering is performed on the back of the laser-treated battery at a sintering temperature of 700-1000°C and a sintering time of 8-15 minutes; The metal slurry, by mass percentage, includes 50-60% silver powder, 30-40% glass powder, 5-10% lead powder, and 5-10% organic additives.
[0007] As a preferred embodiment of the present invention, the tunneling oxide layer material is silicon dioxide or other high dielectric constant materials, which are prepared by atomic layer deposition method.
[0008] As a preferred embodiment of the present invention, the polysilicon doping layer material is n-type or p-type doped polysilicon, which is prepared by chemical vapor deposition or physical vapor deposition.
[0009] As a preferred embodiment of the present invention, the anti-reflection layer material is aluminum oxide and / or silicon nitride, and the anti-reflection layer is a single layer or a stack of aluminum oxide and silicon nitride, and is prepared by plasma enhanced chemical vapor deposition.
[0010] As a preferred embodiment of the present invention, in the laser precision irradiation treatment, a high energy density and controllable laser device is used, including a continuous wave laser, a pulsed laser or an ultrashort pulse laser. The laser wavelength emitted by the laser source is a near-infrared laser in the range of 800-1068 nanometers, the pulse width is set at 50-200ns, the frequency is 10-30kHz, and the laser beam scanning speed is 50-200mm / s.
[0011] As a preferred embodiment of the present invention, the laser device is equipped with a processing system, which includes a high-energy-density and controllable laser source and a control system for controlling the laser beam scanning path, power, and spot size parameters.
[0012] As a preferred embodiment of the present invention, in the low penetration sintering to complete the electrode metallization, the sintering atmosphere is an inert gas, including nitrogen, argon, and a reducing atmosphere.
[0013] As a preferred embodiment of the present invention, the metal slurry further comprises other metal powders or nanoparticles, the other metal powders include copper powder and aluminum powder, and the nanoparticles include carbon nanotubes and graphene.
[0014] As a preferred embodiment of the present invention, before the tunneling oxide layer and the doped polysilicon layer are prepared, the back side of the TOPCon solar cell is also pre-treated, ie, cleaned and deoxidized.
[0015] As a preferred embodiment of the present invention, after the back side of the TOPCon solar cell is subjected to electrode metallization, its saturation current density (J0,met) is lower than 50fA / cm² and its contact resistivity is lower than 1mΩ·cm².
[0016] The beneficial effects achieved by the present invention are: 1. The present invention realizes high-efficiency, low-resistance metallization of the back electrode by introducing laser irradiation combined with a metal paste system of a specific ratio and low-penetration sintering, thereby significantly improving the photoelectric conversion efficiency of solar cells. By precisely controlling the laser irradiation and sintering process, the laser energy acts on the pre-sintered metal paste to promote the mutual diffusion of Ag-Si, forming high-density, small-sized point contacts, while preventing large silver crystals from penetrating the anti-reflection layer, which can reduce the contact resistivity and composite current of the back electrode, so that the saturation current density (J0,met) of the battery is reduced to less than 50fA / cm², and the contact resistivity is less than 1mΩ·cm², thereby effectively improving the open circuit voltage and fill factor of the battery, and ultimately improving the conversion efficiency of the battery. Compared with traditional methods, it can bring a 0.1-0.2% improvement in battery conversion efficiency and improve the performance of TOPCon solar cells.
[0017] 2. The present invention uses a high-energy-density and controllable laser beam to precisely irradiate the pre-sintered metal slurry layer. By precisely adjusting parameters such as laser power, pulse width, frequency and scanning speed, precise control of the burn-through depth of the anti-reflection layer is achieved to avoid damage to the doped polysilicon layer and ensure good contact effects. The forward bias voltage applied during the laser treatment process helps to promote the formation of ohmic contact between the metal and the silicon substrate, reduce interface recombination, thereby reducing the recombination current and improving the performance stability of the battery.
[0018] 3. The present invention adjusts the composition ratio of the metal paste, increases the content of silver powder and optimizes the ratio of glass powder, lead powder and organic additives to prepare a special silver paste fine grid paste, so that it has better sintering performance, lower contact resistance and good adhesion.
[0019] 4. The metallization method of the present invention adopts silver paste fine grid for metallization. At the same time, due to the precise control of the laser processing process, the scrap rate in the production process is reduced, the yield rate is improved, and the production cost is reduced.
[0020] 5. In the low penetration sintering step, the present invention uses an inert gas or a reducing atmosphere as the sintering atmosphere, which helps to protect the metal slurry and the silicon substrate from adverse factors such as oxidation, improves the environmental adaptability of the battery, and enables TOPCon solar cells to maintain stable performance in a wider range of application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The figure is a schematic diagram of the process of the TOPCon solar cell back electrode metallization method adopted in the present invention. DETAILED DESCRIPTION
[0022] The present invention is further described in detail below in conjunction with specific embodiments.
[0023] The TOPCon solar cells used in the following examples are pre-treated, specifically including: Cleaning: Select a TOPCon solar cell, perform preliminary cleaning to remove dust on the back, soak it in a diluted hydrofluoric acid solution for 30 seconds to remove metal ions and oxides on the surface, rinse it with deionized water, and blow it dry with nitrogen; Deoxidation treatment: A plasma cleaner is used to perform deep deoxidation treatment on the back of the cleaned battery. The power of the plasma cleaner is set to 500W, the treatment time is 60 seconds, and the working gas is a mixture of argon and oxygen (ratio 9:1) to remove residual oxides and activate the surface, which is conducive to the adhesion of subsequent layers.
[0024] Example 1: A method for metallizing the back electrode of a TOPCon solar cell, such as Figure 1 As shown, the following steps are included: (1) Using silicon dioxide as the tunneling oxide layer material, an atomic layer deposition technique was used to deposit a 1.5 nm thick tunneling oxide layer on the back of the TOPCon solar cell. The precursors of the ALD equipment were set to tetraethyl orthosilicate and water vapor, the deposition temperature was 200 °C, each cycle was 1 second, and a total of 150 cycles were performed. Select n-type doped polysilicon, and use chemical vapor deposition (CVD) technology to deposit a 75nm thick n-type doped polysilicon layer on the tunnel oxide layer. Set the reaction gas of the CVD equipment to silane and phosphine, the deposition temperature to 650°C, the pressure to 100mTorr, and the duration to 10 minutes; Alumina is used as the anti-reflection layer material, and a 15nm thick aluminum oxide anti-reflection layer is deposited on the polysilicon layer using plasma enhanced chemical vapor deposition (PECVD) technology. The reaction gases of the PECVD equipment are set to trimethylaluminum and oxygen, the deposition temperature is 250°C, the RF power is 150W, and the deposition time is 2 minutes.
[0025] (2) According to mass percentage, 55% of silver powder, 35% of glass powder, 7% of lead powder, and 3% of organic additives are mixed uniformly to prepare a metal slurry; Use a screen printer to evenly coat the prepared metal slurry on the anti-reflection layer on the back of the battery to form a metal slurry layer with a thickness of 20 μm; The battery coated with the metal slurry was placed in a sintering furnace and preliminarily sintered in a nitrogen atmosphere. The sintering temperature was set to 200° C. and the duration was 3 minutes to volatilize the organic additives in the metal slurry and preliminarily solidify the metal layer.
[0026] (3) A high energy density and controllable pulse laser device was selected, with a laser wavelength of 980 nanometers, a laser power of 8 W, a pulse width of 100 ns, and a frequency of 20 kHz; The laser beam scanned the pre-sintered metal paste layer at a speed of 50 mm / s while applying a forward bias voltage of 1 V for a duration of 2 seconds.
[0027] (4) Place the laser-treated battery in a sintering furnace and perform low penetration sintering in a nitrogen atmosphere. Set the sintering temperature to 850°C and the sintering time to 15 minutes.
[0028] Example 2: A method for metallizing the back electrode of a TOPCon solar cell, such as Figure 1 As shown, the following steps are included: (1) Using hafnium oxide as the tunneling oxide layer material, an atomic layer deposition technique was used to deposit a 1.2 nm thick tunneling oxide layer on the back of the TOPCon solar cell. The precursors of the ALD equipment were set to tetraethyl orthosilicate and water vapor, the deposition temperature was set to 250°C, and each cycle was 0.8 seconds, for a total of 200 cycles. Select p-type doped polysilicon, and use physical vapor deposition (PVD) technology to deposit a p-type doped polysilicon layer with a thickness of 80nm on the tunnel oxide layer. Set the target material of the PVD equipment to a boron-doped silicon target, the deposition temperature to 600℃, the pressure to 50mTorr, and the duration to 12 minutes; Silicon nitride is used as the anti-reflection layer material, and a 20nm thick silicon nitride anti-reflection layer is deposited on the polysilicon layer using plasma enhanced chemical vapor deposition (PECVD) technology. The reaction gases of the PECVD equipment are set to silane, ammonia and nitrogen, the deposition temperature is 300°C, the RF power is 200W, and the deposition time is 3 minutes.
[0029] (2) uniformly mixing 58% of silver powder, 32% of glass powder, 5% of lead powder, 3% of organic additives and 2% of carbon nanotubes according to mass percentage to prepare a metal slurry; Use a screen printer to evenly coat the prepared metal slurry on the anti-reflection layer on the back of the battery to form a metal slurry layer with a thickness of 18 μm; The battery coated with the metal slurry was placed in a sintering furnace and preliminarily sintered in a nitrogen atmosphere. The sintering temperature was set to 200° C. and the duration was 3 minutes to volatilize the organic additives in the metal slurry and preliminarily solidify the metal layer.
[0030] (3) Select an ultrashort pulse laser device with a laser wavelength of 1030 nanometers, a laser power of 10 W, a pulse width of 50 ns, and a frequency of 30 kHz; The laser beam scanned the pre-sintered metal paste layer at a speed of 100 mm / s while applying a forward bias voltage of 0.8 V for a duration of 1 second.
[0031] (4) The laser-treated battery was placed in a sintering furnace and subjected to low penetration sintering in a nitrogen atmosphere. The sintering temperature was set to 900 °C and the sintering time was set to 10 min.
[0032] Embodiment 3: A method for metallizing the back electrode of a TOPCon solar cell, such as Figure 1 As shown, the following steps are included: (1) Using silicon dioxide as the tunneling oxide layer material, an atomic layer deposition technique was used to deposit a 1.8 nm thick tunneling oxide layer on the back of the TOPCon solar cell. The precursors of the ALD equipment were set to tetraethyl orthosilicate and water vapor, the deposition temperature was 200 °C, each cycle was 1 second, and a total of 150 cycles were performed. Select n-type doped polysilicon, and use electron beam evaporation technology in physical vapor deposition (PVD) to deposit a 60nm thick n-type doped polysilicon layer on the tunneling oxide layer. The dopant is phosphorus, the evaporation temperature is 1200℃, and the vacuum degree is 1×10⁻ 6 Torr, the deposition time is 8 minutes; A stack of silicon nitride and aluminum oxide is used as the anti-reflection layer material. First, a 10 nm thick silicon nitride layer is deposited on the polysilicon layer using plasma enhanced chemical vapor deposition (PECVD) technology, and then a 5 nm thick aluminum oxide layer is deposited. The specific conditions are adjusted with reference to the PECVD parameters in Examples 1 and 2.
[0033] (2) According to mass percentage, 60% of silver powder, 30% of glass powder, 5% of lead powder, and 5% of organic additive are mixed uniformly to prepare a metal slurry; Use a screen printer to evenly coat the prepared metal slurry on the anti-reflection layer on the back of the battery to form a metal slurry layer with a thickness of 22 μm; The battery coated with the metal slurry was placed in a sintering furnace and preliminarily sintered in a nitrogen atmosphere. The sintering temperature was set to 250° C. and the duration was 4 minutes to volatilize the organic additives in the metal slurry and preliminarily solidify the metal layer.
[0034] (3) A continuous laser device with a laser wavelength of 940 nanometers and a laser power of 6 W is selected to continuously irradiate the pre-sintered metal slurry layer, while applying a forward bias voltage of 1.2 V for a duration of 1.5 seconds.
[0035] (4) The laser-treated battery was placed in a sintering furnace and subjected to low penetration sintering in a nitrogen atmosphere. The sintering temperature was set to 750 °C and the sintering time was set to 12 min.
[0036] Comparative Example: A conventional TOPCon solar cell back electrode metallization method, compared with Example 1, uses conventional metal silver paste and sintering treatment, that is, does not use laser equipment to irradiate the pre-sintered metal paste layer, and the specific steps are: (1) Using silicon dioxide as the tunneling oxide layer material, a 1.5 nm thick tunneling oxide layer was deposited on the back of the battery using atomic layer deposition technology. The precursors of the ALD equipment were set to tetraethyl orthosilicate and water vapor, the deposition temperature was 200 °C, each cycle was 1 second, and a total of 150 cycles were performed; Select n-type doped polysilicon, and use chemical vapor deposition (CVD) technology to deposit a 75nm thick n-type doped polysilicon layer on the tunnel oxide layer. Set the reaction gas of the CVD equipment to silane and phosphine, the deposition temperature to 650°C, the pressure to 100mTorr, and the duration to 10 minutes; Alumina is used as the anti-reflection layer material, and a 15nm thick aluminum oxide anti-reflection layer is deposited on the polysilicon layer using plasma enhanced chemical vapor deposition (PECVD) technology. The reaction gases of the PECVD equipment are set to trimethylaluminum and oxygen, the deposition temperature is 250°C, the RF power is 150W, and the deposition time is 2 minutes.
[0037] (2) According to the mass percentage, 67% of silver powder, 30% of glass powder, and 3% of organic additives are uniformly mixed to prepare a metal slurry; Use a screen printer to evenly coat the prepared metal slurry on the anti-reflection layer on the back of the battery to form a metal slurry layer with a thickness of 20 μm; The battery coated with the metal slurry was placed in a sintering furnace and sintered in a nitrogen atmosphere at a sintering temperature of 850° C. for 15 minutes.
[0038] Performance test: The TOPCon solar cells with metallized back electrodes in Examples 1 to 3 and the comparative example were subjected to relevant performance tests, and the results are shown in Table 1; Table 1 TOPCon solar cell performance test results It can be seen from Table 1 that the materials and technologies (metal slurry, laser treatment, low-penetration sintering, etc.) used in the examples can significantly improve the open circuit voltage, short circuit current, fill factor and conversion efficiency of the battery; wherein, the laser treatment step is adopted in Example 1, which helps to reduce the contact resistance and improve the fill factor, thereby improving the conversion efficiency; Example 2 adopts different tunneling oxide layer materials (hafnium oxide) and anti-reflection layer materials (silicon nitride), as well as higher sintering temperatures and shorter sintering times, which helps to optimize the battery performance, especially in terms of open circuit voltage and short circuit current; Example 3 combines PVD technology and laminated anti-reflection layer design to further improve the light absorption capacity and conductivity of the battery, thereby slightly improving various performance indicators. In comparison, the various performances of the comparative example have certain limitations.
[0039] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for metallizing the back electrode of a TOPCon solar cell, characterized in that: The following steps are involved: (1) Preparation of tunnel oxide layer and doped polysilicon layer: First, a tunnel oxide layer with a thickness of 1-2 nm is formed on the back of the TOPCon solar cell; a doped polysilicon layer with a thickness of 50-100 nm is deposited on the tunnel oxide layer; and an anti-reflection layer with a thickness of 5-30 nm is deposited on the polysilicon layer; (2) Metal slurry layer coating and preliminary sintering: Use screen printing to coat the metal slurry on the anti-reflection layer on the back to form a metal slurry layer with a thickness of 15-25 μm, and perform preliminary sintering in a nitrogen atmosphere at a preliminary sintering temperature of 150-300 °C; (3) Laser precision irradiation treatment: Use laser equipment to precisely irradiate the pre-sintered metal slurry layer, with a duration of 200ms-3s, a laser power of 5-10W, and a forward bias voltage of 0.5-1.5V; (4) Low penetration sintering to complete electrode metallization: low penetration sintering is performed on the back of the laser-treated battery at a sintering temperature of 700-1000°C and a sintering time of 8-15 minutes; The metal slurry, by mass percentage, includes 50-60% silver powder, 30-40% glass powder, 5-10% lead powder, and 5-10% organic additives.
2. A TOPCon solar cell back electrode metallization method according to claim 1, characterized in that: The tunneling oxide layer material is silicon dioxide or other high dielectric constant materials, and is prepared by an atomic layer deposition method.
3. A TOPCon solar cell back electrode metallization method according to claim 1, characterized in that: The polysilicon doping layer material is n-type or p-type doped polysilicon, which is prepared by chemical vapor deposition or physical vapor deposition.
4. A TOPCon solar cell back electrode metallization method according to claim 1, characterized in that: The anti-reflection layer material is aluminum oxide and / or silicon nitride. The anti-reflection layer is a single layer or a stack of aluminum oxide and silicon nitride, and is prepared by a plasma enhanced chemical vapor deposition method.
5. A TOPCon solar cell back electrode metallization method according to claim 1, characterized in that: In the laser precision irradiation treatment, a high energy density and controllable laser device is used, including a continuous wave laser, a pulse laser or an ultrashort pulse laser. The laser wavelength emitted by the laser source is a near-infrared laser in the range of 800-1068 nanometers, the pulse width is set at 50-200ns, the frequency is 10-30kHz, and the laser beam scanning speed is 50-200mm / s.
6. A method for metallizing the back electrode of a TOPCon solar cell according to claim 5, characterized in that: The laser device is equipped with a processing system, which includes a high-energy-density and controllable laser source and a control system for controlling the laser beam scanning path, power, and spot size parameters.
7. A TOPCon solar cell back electrode metallization method according to claim 1, characterized in that: In the low penetration sintering to complete the electrode metallization, the sintering atmosphere is an inert gas, including nitrogen, argon, and a reducing atmosphere.
8. A TOPCon solar cell back electrode metallization method according to claim 1, characterized in that: The metal slurry further comprises other metal powders or nanoparticles. The other metal powders include copper powder and aluminum powder. The nanoparticles include carbon nanotubes and graphene.
9. A TOPCon solar cell back electrode metallization method according to claim 1, characterized in that: Before the tunnel oxide layer and the doped polysilicon layer are prepared, the back side of the TOPCon solar cell is pre-treated, that is, cleaned and deoxidized.
10. A TOPCon solar cell back electrode metallization method according to claim 1, characterized in that: After the back side of the TOPCon solar cell is metallized with electrodes, its saturation current density is lower than 50fA / cm² and its contact resistivity is lower than 1mΩ·cm².
Citation Information
Patent Citations
Solar cell manufacturing method
CN104704639A
Crystalline silicon solar cell laser sintering method
CN116705903A
Post-treatment process of metal electrode of solar cell and preparation method of solar cell
CN118919601A
Method for manufacturing solar cell of solar module, involves forming front-side contacts on dielectric layer on front side of substrate while ensuring partial melting and strengthening of rear side contacts, by applying metallization
DE102011052261A1
Solar cell and method for manufacturing the same
KR1020120026777A
Cited By
Method for improving reliability of laser-assisted sintering of solar cell and solar cell
CN121038427A